2011
DOI: 10.1038/ijo.2011.99
|View full text |Cite
|
Sign up to set email alerts
|

Advances in physical activity monitoring and lifestyle interventions in obesity: a review

Abstract: Obesity represents a strong risk factor for developing chronic diseases. Strategies for disease prevention often promote lifestyle changes encouraging participation in physical activity. However, determining what amount of physical activity is necessary for achieving specific health benefits has been hampered by the lack of accurate instruments for monitoring physical activity and the related physiological outcomes. This review aims at presenting recent advances in activity-monitoring technology and their appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 82 publications
1
69
0
Order By: Relevance
“…These studies concluded that the duration of exercise (150 min) is more important than the intensity (moderate vs. vigorous), but these studies did not include patients with BMI > 40 kg/m 2 [ 70 ]. The rise of new technologies on the development and marketing of instruments to measure the amount of physical activity (pedometers, accelerometers) will undoubtedly help to better determine the amount of physical activity needed to optimize the dose-response results on physical activitybased interventions [ 71 ].…”
Section: Recommendations For Physical Activitymentioning
confidence: 96%
“…These studies concluded that the duration of exercise (150 min) is more important than the intensity (moderate vs. vigorous), but these studies did not include patients with BMI > 40 kg/m 2 [ 70 ]. The rise of new technologies on the development and marketing of instruments to measure the amount of physical activity (pedometers, accelerometers) will undoubtedly help to better determine the amount of physical activity needed to optimize the dose-response results on physical activitybased interventions [ 71 ].…”
Section: Recommendations For Physical Activitymentioning
confidence: 96%
“…These novel techniques can measure the engagement in specific activity types [51]. Integrated into T2DM therapy, the therapy adherence to physical activity lifestyle interventions could be monitored.…”
Section: Carbohydrate Estimationmentioning
confidence: 99%
“…[11][12][13][14] The newest generation accelerometers can monitor sedentary behavior and specific activity types to evaluate the effectiveness of lifestyle interventions for health promotion. 15 In conclusion, O'Dwyer and Coote attempt to help clinicians choose an optimal tool to measure physical activity. They correctly state that self-report methods are not reliable and that motion sensors are the best option.…”
mentioning
confidence: 98%